PERAN BMT DALAM MENGATASI KETIMPANGAN EKONOMI, MEMBANGUN INKLUSI KEUANGAN DI ERA DIGITAL - Rizky Fauzi, Abiseka Sahal; Wibiksana, M Rangga; Ramandini, Nurul; Rofi, Hafidz Ainur (Media Riset Bisnis Ekonomi Sains dan Terapan, 2024)
The digital transformation of the financial sector has created significant opportunities for Baitul Maal wa Tamwil (BMT) to enhance financial inclusion and expand services to unbanked communities. This study examines the role of digitalization in improving BMT's operational efficiency, the challenges faced, and strategic opportunities in the digital economy era. The findings indicate that the adoption of mobile applications, management information systems (MIS), business process digitalization, and partnerships with fintech has improved financial accessibility and supported the growth of micro, small, and medium enterprises (MSMEs).However, digitalization also presents several challenges, including digital disparities, cybersecurity risks, high implementation costs, and regulatory adaptation. Therefore, effective strategies such as enhancing digital literacy, investing in cybersecurity, and fostering collaboration with government and fintech are crucial for ensuring the sustainability of BMT’s digital transformation. With the right approach, BMT can not only strengthen its competitiveness in the microfinance sector but also play a greater role in fostering a more inclusive, equitable, and sustainable economy in Indonesia.Keywords: Baitul Maal wa Tamwil (BMT), financial inclusion, digitalization, fintech, microfinance.